2021
DOI: 10.3390/ma14206093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Properties of Aggregates on the Mechanical Properties of High Strength Concrete under Loading and High Temperature Conditions

Abstract: The effect of the thermal properties of aggregates on the mechanical properties of high-strength concrete was evaluated under loading and high-temperature conditions. For the concrete, granite was selected as a natural aggregate, and ash-clay and clay as lightweight aggregates. The mechanical properties of the concrete (stress–strain, compressive strength, elastic modulus, thermal strain, and transient creep) were evaluated experimentally under uniform heating from 20 to 700 °C while maintaining the load at 0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Regardless of specimen type, the strength decreased with the increasing temperature. This is due to the presence of internal cracks inside the specimen resulting from the increasing internal pressures and stresses from the water being heated and the expansion of the fine aggregates [ 74 , 75 , 76 ]. Tufail et al [ 77 ] indicated that the differential thermal expansion between cement paste and aggregates led to decreases in compressive strength under high temperature due to internal stresses.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of specimen type, the strength decreased with the increasing temperature. This is due to the presence of internal cracks inside the specimen resulting from the increasing internal pressures and stresses from the water being heated and the expansion of the fine aggregates [ 74 , 75 , 76 ]. Tufail et al [ 77 ] indicated that the differential thermal expansion between cement paste and aggregates led to decreases in compressive strength under high temperature due to internal stresses.…”
Section: Resultsmentioning
confidence: 99%
“…Strength degradation was observed up to 200 °C, followed by a slight strength recovery between 200 and 300 °C. According to Lee et al, the vapor pressure and thermal expansion of aggregates generally affect the strength recovery at 200 to 300 °C [ 27 , 28 , 29 , 30 ]. Roufael et al reported slight strength loss up to 150 °C and slight strength increase in the 150–300 °C range [ 14 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the temperature range below 300 • C, LC41 and LC33 showed a higher peak strain than NC41 and NC33, whereas NC28 exhibited a higher peak strain than LC28. Above 500 • C, the peak strain sharply increased [32], ranging from 0.0058 to 0.0063 at 500 • C and from 0.0094 to 0.012 at 700 • C. At 700 • C, NC exhibited a higher peak strain than LC at all levels, indicating the significant influence of crushed granite aggregate with a relatively higher stiffness than that of coal-ash aggregate, which is more porous and of low density (see Table 1) [31].…”
Section: Stress-strain Analysis Of Nc and Lc After High Temperature E...mentioning
confidence: 98%
“…At 700 • C, ductile failure occurred with a strain of approximately 0.01. NC showed a failure strain at a relatively higher stress compared to LC at the same target temperature, indicating that the stress at the aggregate-paste interface improved with crushed granite aggregate, which has a relatively high roughness [31]. Figure 9 shows the peak strain of NC and LC after high temperature exposure.…”
Section: Stress-strain Analysis Of Nc and Lc After High Temperature E...mentioning
confidence: 99%